Workers of a drywood termite do not work - Korb, Judith (BioMed Central, 2007)
BACKGROUND: Social insects (ants, bees, wasps and termites) are considered as prime examples of altruism in which individuals (workers) forego their own reproduction to help other individuals reproduce. Such a behaviour is favoured by natural selection because the workers rear close kin and in doing so enhance their inclusive fitness. RESULTS: Here I show, however, that this does not generally apply to termite workers which are scarcely investigated. In the basal drywood termite Cryptotermes secundus the 'workers', which form the large majority of a colony, did not stay to raise relatives. There is no brood caring behaviour and they do not engage in costly help. They are large immature offspring that develop into either winged (dispersing) or unwinged (replacement) reproductives and the probability that they did so was unaffected by the number of brood in the nest as a brood addition experiment showed. CONCLUSION: Thus, in contrast to general perception where termite workers are considered equivalent to workers in Hymenoptera, the 'large immatures' of C. secundus did not behave as workers that help in raising younger siblings. This apparently is not necessary as the colony lives inside its food. These results, which are likely to be typical for wood-dwelling termites, open the possibility that large complex group living can evolve without altruistic helping and that costly altruistic helping by workers in termites evolved only as a second step.